Observations on some nematodes parasitic in freshwater fishes in Laos - Moravec, F; Scholz, T (Folia parasitologica, 1991)
In 1989, samples of some freshwater fishes collected in Vientiane Province (R. Mekong basin) in Laos were examined for helminths. This material comprised 11 species of parasitic nematodes (7 adults and 4 larvae), including 3 species new to science: Camallanus (Camallanus) hampalae sp. n. from Hampala macrolepidota, Procamallanus (Punctocamallanus) punctatus sp. n. from Mystus rhegma and Mystus sp., and Rhabdochona (Globochona) equispiculata sp. n. from Hampala macrolepidota and H. dispar. Zeylanema Yeh, 1960 is considered a subgenus of the genus Camallanus, Dentocamallanus subgen. n. (type species C. (D.) sweeti (Moorthy, 1937)) is proposed for the species of Paracamallanus with teeth in the buccal capsule, and Punctocamallanus subgen. n. (type species P. (P.) punctatus sp. n.) for the species of Procamallanus with the buccal capsule ornamented with punctations. The name Rhabdochona wangi nom. nov. is proposed for R. bagarii Wang et Guo, 1983 (a homonym to R. bagarii Gupta et Srivastava, 1982) and Camallanus gomtii Gupta et Verma, 1978 is newly synonymized with Neocamallanus ophiocephali (Pearse, 1933). All the nematodes are recorded from Laos for the first time. The parasites are briefly described and illustrated and some problems concerning their taxonomy and geographical distribution are discussed.
Keywords: Nematode Infections; Animals; Nematoda; Laos; Female; ženské pohlaví; nemoci ryb; nematodózy; Fish Diseases; Fishes; ryby; Fresh Water; hlístice; Male; sladká voda; Larva; zvířata; mužské pohlaví; larva